Genome-wide analysis reveals extensive functional interaction between DNA replication initiation and transcription in the genome of Trypanosoma brucei. - Tiengwe, C; Marcello, L; Farr, H; Dickens, N; Kelly, S; Swiderski, M; Vaughan, D; Gull, K; Barry, J; Bell, S; McCulloch, R (Cell Press, 2012)
Identification of replication initiation sites, termed origins, is a crucial step in understanding genome transmission in any organism. Transcription of the Trypanosoma brucei genome is highly unusual, with each chromosome comprising a few discrete transcription units. To understand how DNA replication occurs in the context of such organization, we have performed genome-wide mapping of the binding sites of the replication initiator ORC1/CDC6 and have identified replication origins, revealing that both localize to the boundaries of the transcription units. A remarkably small number of active origins is seen, whose spacing is greater than in any other eukaryote. We show that replication and transcription in T. brucei have a profound functional overlap, as reducing ORC1/CDC6 levels leads to genome-wide increases in mRNA levels arising from the boundaries of the transcription units. In addition, ORC1/CDC6 loss causes derepression of silent Variant Surface Glycoprotein genes, which are critical for host immune evasion.